2002
DOI: 10.1046/j.1471-8286.2002.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite loci from the pink shrimp Farfantenaeus notialis (Crustacea, Decapoda)

Abstract: Farfantepenaeus notialis is an important resource for fisheries in Cuba. For this reason and for a sustainable exploitation it is important to study their population structure and genetic variability. We report and characterize microsatellites as genetic markers from this species. Fifteen microsatellite polymerase chain reaction (PCR) primers were designed and tested in some individuals from different populations. Seven pair of primers showed reliable amplification products and five were polymorphic. The allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
(7 reference statements)
2
4
0
Order By: Relevance
“…Despite the observed exceptions, similar to those reported for other crustaceans and insects (Robainas et al, 2003), microsatellites containing dinucleotide repetitions seem to be the most frequent among penaeid shrimp, followed by microsatellites containing trinucleotides. Moreover, even though a few motifs of all the analyzed classes may appear at greater abundance, there is a pronounced variability within and between species, indicating the high differentiation dynamism of these repetitions within this animal group.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…Despite the observed exceptions, similar to those reported for other crustaceans and insects (Robainas et al, 2003), microsatellites containing dinucleotide repetitions seem to be the most frequent among penaeid shrimp, followed by microsatellites containing trinucleotides. Moreover, even though a few motifs of all the analyzed classes may appear at greater abundance, there is a pronounced variability within and between species, indicating the high differentiation dynamism of these repetitions within this animal group.…”
Section: Introductionsupporting
confidence: 84%
“…However, the motifs TA (24%) in L. vannamei and TC and CA that appeared in equal proportion (6%) in P. monodon were the most abundant, differing from those observed when the set of all species is considered. The tetranucleotides were also abundant in the compound microsatellites of both species, corroborating the results that considered the entire penaeid set.Despite the observed exceptions, similar to those reported for other crustaceans and insects (Robainas et al, 2003), microsatellites containing dinucleotide repetitions seem to be the most frequent among penaeid shrimp, followed by microsatellites containing trinucleotides. Moreover, even though a few motifs of all the analyzed classes may appear at greater abundance, there is a pronounced variability within and between species, indicating the high differentiation dynamism of these repetitions within this animal group.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…In the present study, all five studied microsatellite loci revealed the varied degree of polymorphism, significant differences in the genetic heterogeneity and allele frequencies. Also, Robainas, Monnerot, Solignac, Dennebouy, and Espinosa (2002) by evaluation the genetic variability from the pink shrimp Farfantenaeus notialis (Crustacea, Decapoda) in Cuba reported seven pairs of their primers showed reliable amplification products and five of them was polymorphic. The maximum of heterozygosity was found in white shrimp samples from Lifeh-Boosif populations that indicated, the studied populations have rich genetic diversity based on allelic variation.…”
Section: Discussionmentioning
confidence: 99%